Acupuncture for babies, children and teenagers : treating both the illness and the child - Avern, Rebecca (Singing Dragon, an imprint of Jessica Kingsley Publishers, 2019)
This colour textbook enables acupuncturists to diagnose and treat physical and emotional ailments in babies, children and teenagers. It draws on the author's extensive clinical experience to provide solutions to a wide range of conditions including asthma, allergies, bedwetting, digestive issues, ADHD and depression.